Special education teachers' use of AI to support students with disabilities in writing - Goldman, Samantha R.; Smith, Sean J.; Carreon, Adam (Frontiers in Education, 2025)
IntroductionAdvancements in artificial intelligence (AI) have the potential to augment and alter writing instruction and the supports available to struggling writers and those with learning disabilities. Yet research continues to show that special education teachers do not feel prepared to integrate technology into writing instruction, despite evidence supporting its use to improve writing outcomes for students with disabilities.MethodsThis study surveyed 420 high-incidence special education teachers nationwide using the Preparation to Integrate Writing and Technology in Special Education for Teachers Scale (PIWTSE-T), a validated measure. Data analysis included descriptive statistics, Pearson and Spearman correlations, multiple regression, and ANOVA to examine AI integration and its predictors.ResultsDescriptive results indicated that special education teachers rarely use AI tools at any stage of the writing process. Multiple regression revealed that teachers' attitudes toward AI were the strongest predictor of AI use. A final regression model identified three significant predictors—AI use to support student learning (AISS), AI use to support teaching practice (AITP), and preparation to integrate technology into writing (PITW), explaining 53% of the variance in AI integration.DiscussionThis study adds to the growing body of literature highlighting the need for special education teacher preparation programs to strengthen their efforts to prepare educators to leverage technology, specifically AI, as a tool for evidence-based writing instruction. Future research should focus on developing and refining teacher-training models that leverage technology to improve writing outcomes for students with disabilities.